Non-alcoholic fatty liver disease promotes breast cancer progression through upregulated hepatic fibroblast growth factor 21 - Yue Sui; Qingqing Liu; Cong Xu; Kumar Ganesan; Zhen Ye; Yan Li; Jianmin Wu; Bing Du; Fei Gao; Cailu Song; Jianping Chen (Cell Death and Disease, 2024)
Abstract Non-alcoholic fatty liver disease (NAFLD) has been shown to influence breast cancer progression, but the underlying mechanisms remain unclear. In this study, we investigated the impact of NAFLD on breast cancer tumor growth and cell viability through the potential mediator, hepatic fibroblast growth factor 21 (FGF21). Both peritumoral and systemic administration of FGF21 promoted breast cancer tumor growth, while FGF21 knockout attenuated the tumor-promoting effects of the high-fat diet. Mechanistically, exogenous FGF21 treatment enhanced the anti-apoptotic ability of breast cancer cells through STAT3 and Akt/FoXO1 signaling pathways, and mitigated doxorubicin-induced cell death. Furthermore, we observed overexpression of FGF21 in tumor tissues from breast cancer patients, which was associated with poor prognosis. These findings suggest a novel role for FGF21 as an upregulated mediator in the context of NAFLD, promoting breast cancer development and highlighting its potential as a therapeutic target for cancer treatment.